The cockroach - McEwan, Ian (Anchor Books, a division of Penguin Random House LLC, 2019)
Jim Sams has undergone a metamorphosis. In his previous life he was ignored or loathed, but in his new incarnation he is the most powerful man in Britain--and it is his mission to carry out the will of the people. Nothing must get in his way: not the opposition, nor the dissenters within his own party. Not even the rules of parliamentary democracy.